An Evidence-Based Review on the Role of Gut-Brain Axis in Neurological and Psychiatric Disorders: Review Article (Journal of Pharma Insights and Research, 2025)
The gut microbiota plays an important role in maintaining neurological and mental health through the gut-brain axis. Microbial dysbiosis is regarded as a significant factor in the pathogenesis of neurological and psychiatric disorders, necessitating a thorough study of these connections. A systematic search of PubMed and ScienceDirect databases was conducted for articles published between 2015 and March 2025. This review focused on studies investigating gut-brain axis involvement in neurological and psychiatric disorders, particularly examining immune modulation, neurotransmitter regulation, and inflammatory pathways. Significant alterations in gut microbiota composition were observed across multiple disorders. Parkinson's disease patients showed decreased Lactobacillus and Bacteroides levels, while Alzheimer's disease patients exhibited reduced microbial diversity and diminished short-chain fatty acid production. Major depressive disorder was characterized by increased Firmicutes-to-Bacteroidetes ratio and altered tryptophan metabolism. Social anxiety disorder showed correlations with specific microbial patterns, particularly reduced Lactobacillus abundance. These alterations were linked to increased inflammatory markers, disrupted neurotransmitter synthesis, and compromised blood-brain barrier integrity. The evidence establishes strong mechanistic links between gut microbiota alterations and neurological/psychiatric pathologies. Therapeutic interventions targeting the gut microbiome show promise, though more clinical trials are needed to establish optimal treatment protocols. Clinical studies should focus on developing personalized microbiome-based therapies and validating their long-term efficacy